2010
DOI: 10.1677/joe-10-0102
|View full text |Cite
|
Sign up to set email alerts
|

An IGF1/insulin receptor substrate-1 pathway stimulates a mitotic kinase (cdk1) in the uterine epithelium during the proliferative response to estradiol

Abstract: Estrogens are potent mitogens for some target organs, such as the uterus, and cancers that develop in this organ might be linked to the proliferative action of these hormones. However, the mechanism by which estrogens influence the cell cycle machinery is not known. We found that a null mutation for the insulin receptor substrate (IRS)-1, a docking protein that is important for IGF-1 signaling, compromised hormone-induced mitosis in the uterine epithelium; BrdU incorporation was not affected. This selective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In contrast for PS animals, our WB analyses detected down-regulated IRS-1 expression at the whole organ level (also down-regulated at the mRNA level) that, according to our IHC analyses, involved: 1) lack of signal in the endometrial epithelial compartment of both treatment groups and 2) down-regulated cytoplasm/ECM signal in the stromal/mesenchymal compartment. Further investigations are needed in order to reconcile these observations with the general regulatory and tumor biology considerations listed above and with the complex biochemical pathways with which IRS-1 is implicated in estrogen-induced cell proliferation in the uterus [76]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast for PS animals, our WB analyses detected down-regulated IRS-1 expression at the whole organ level (also down-regulated at the mRNA level) that, according to our IHC analyses, involved: 1) lack of signal in the endometrial epithelial compartment of both treatment groups and 2) down-regulated cytoplasm/ECM signal in the stromal/mesenchymal compartment. Further investigations are needed in order to reconcile these observations with the general regulatory and tumor biology considerations listed above and with the complex biochemical pathways with which IRS-1 is implicated in estrogen-induced cell proliferation in the uterus [76]. …”
Section: Discussionmentioning
confidence: 99%
“…They proposed a mechanism in which IGF1, produced in the stroma, acts via IGF1R in the epithelium to stimulate activation of PI3K/AKT, which in turn phosphorylates and inactivates GSK3β, allowing nuclear accumulation of cyclin D1 and cell cycle progression. Other groups suggested that IGF1 regulates progression through the G2/M rather than G1 phase of the cell cycle (Adesanya et al ., 1999; Walker et al ., 2010). Whatever the actual mechanism, these studies point to a role of IGF1 in executing E-induced epithelial proliferation by acting in a paracrine manner, as shown in Figure 2.…”
Section: Role Of E and P Receptors During Early Pregnancy: Lessons Lementioning
confidence: 99%
“…The link between IR and cancer may be related to high compensatory levels of insulin. This hormone may increase cell proliferation either directly or by increasing the levels of other more potent growth factors, such as insulin‐like growth factor, which is one of the growth factors responsible for the initial steps of cancer development. However, evidence that IR is the major cause of increased risk of cancer, other than colon cancer, is still inconsistent.…”
Section: Obesity and Comorbiditiesmentioning
confidence: 99%